2006
DOI: 10.1017/s0022029906001798
|View full text |Cite
|
Sign up to set email alerts
|

Economic impacts of reduced milk production associated with papillomatous digital dermatitis in dairy cows in the USA

Abstract: The goal of this study was to measure the economic impacts of reduced milk production associated with papillomatous digital dermatitis (PDD) in dairy cows in the USA, and of specific risk factors for PDD, in 1996. The method applied was an economic-welfare analysis of producer and consumer surplus, with the GUM Workbench used to analyse uncertainties in the measurements. Reduced milk production associated with PDD was found to reduce consumer surplus by Dollars 750 million +/- Dollars 580 million, and to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 17 publications
0
35
0
4
Order By: Relevance
“…The DD lesion is acute to chronic, is painful at palpation, and causes lameness and wasting. The disease was first described to occur in Italy in 1974 (7) and has since been found in many parts of the world, where it now constitutes a significant welfare and production problem (23,27). A bacterial etiology of DD is supported by the observation that cattle infected with DD respond to antibiotic treatment and that virus isolation from affected tissues has been unsuccessful (13).…”
mentioning
confidence: 89%
“…The DD lesion is acute to chronic, is painful at palpation, and causes lameness and wasting. The disease was first described to occur in Italy in 1974 (7) and has since been found in many parts of the world, where it now constitutes a significant welfare and production problem (23,27). A bacterial etiology of DD is supported by the observation that cattle infected with DD respond to antibiotic treatment and that virus isolation from affected tissues has been unsuccessful (13).…”
mentioning
confidence: 89%
“…For both primer sets, thermal cycling using a T3 thermocycler (Biometram, Göttingen, Germany) was performed as follows: denaturation at 94°C for 6 min and 30 cycles of denaturation at 94°C for 45 s, annealing at 57°C for 45 s, and extension at 72°C for 90 s. A final elongation step of 10 min was followed by cooling to 4°C. Positive (DNA) and negative (distilled water [dH 2 O]) controls were included for each PCR setup. The DNA concentration and quality of the PCR amplicons from all samples were assessed with an Agilent 2100 Bioanalyzer (Agilent Technologies Inc. Santa Clara, CA) prior to high-throughput sequencing (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…It has now been more than 30 years since the disease was first recognized, and while regular foot bathing has been shown to have some efficacy, an effective preventative measure or treatment that completely eliminates the disease has yet to be identified (19). The result is that the disease is endemic in cattle across the world, and one recent report suggested that the economic impact resulting from milk production in the United States alone is a loss of as much as $190 million per year (20).…”
mentioning
confidence: 96%